Fire Sales in a Model of Complexity - CABALLERO, RICARDO J.; SIMSEK, ALP (Journal of Finance, 2013)
ABSTRACT We present a model of financial crises that stem from endogenous complexity . We conceptualize complexity as banks' uncertainty about the financial network of cross exposures. As conditions deteriorate, cross exposures generate the possibility of a domino effect of bankruptcies. As this happens, banks face an increasingly complex environment since they need to understand a greater fraction of the financial network to assess their own financial health. Complexity dramatically amplifies banks' perceived counterparty risk, and makes relatively healthy banks reluctant to buy risky assets. The model also features a novel complexity externality .